Chitosan–Moringa Seed Powder Composite Films for Turbidity Coagulation - Chakraborty, Soma (Archīum Ateneo, 2024)
Chitosan, chitosan-moringa seed powder, and chitosan-moringa seed powder-bentonite composite films were fabricated by solvent casting method. The texture and the color of the chitosan films changed in the presence of moringa seed powder and bentonite. Moringa seed powder decreased the tensile strength of the films, whereas bentonite improved the tensile strength of the films when its concentration was below 15 wt%. All the films could efficiently remove turbidity from model turbid water – prepared by dispersing kaolin in water. A marked increase in turbidity coagulation was observed when moringa seed powder was incorporated into the chitosan film. Films with 15 wt% moringa seed powder could remove 73% in 3 h, whereas chitosan film alone removed 53% in 3 h. Further enhancement of turbidity removal efficacy was observed when bentonite was incorporated into the films along with the moringa seed powder. Films with 15 wt% moringa seed powder and 10 wt% bentonite removed 83 and 96% turbidity in 3 and 12 h, respectively. Furthermore, these films could be reused several times. The films with the above composition were tested for turbidity settlement for five cycles. In the 5th cycle, the films could remove 85% turbidity without undergoing any breakage.